Identifying the Attractiveness and Place Branding Strategies in Exhibitions - Majid Mohammad Shafiee (مطالعات مدیریت راهبردی, 2017)
International exhibitions are as one of the most important introducing channelsfor product and transfer of technology in the world. This study has identified the strategic aspects of exhibition destination attractiveness in Isfahan International Exhibition. Participants in this study include exhibitors and visitors. The scale of exhibition destination attractiveness was applied on them. In this paper, Cronbach's alpha and combined research were used for reliability, and exploratory and confirmatory factor analysis for validity. Results revealed that the Cronbach's alpha coefficient for scale of exhibition destination attractiveness was equal to 0.91. For subscales of facilities, availability, city / host region as a competitive source for exhibitors, economic environment, host city leadership in industry and leisure environment was calculated 0.75, 0.85, 0.79, 0.82, 0.81, and 0.78, respectively. The result of confirmatory factor showed that this scale is a second- order constituent made up of facilities, availability, and city / host region as a competitive source for exhibitors, economic environment, host city leadership in industry and leisure environment.